Molecular Epidemiology of Hepatitis C Virus Genotypes in Patients with Thalassemia Major in Golestan Province, Iran - sareh Zhand; Masuod Bazuori; Alijan Tabarraei; Abdolvahab Moradi (Golestan University Of Medical Sciences, 2017)
ABSTRACT Introduction: In Iran, hepatitis C virus (HCV) is the most prevalent cause of chronic hepatitis and cirrhosis in patients with hemophilia, thalassemia, and renal failure. Recent studies suggest that patients infected with different HCV genotypes have different clinical profiles, severity of liver disease and response to therapy. Several molecular methods targeting different HCV genomic regions have been introduced for genotyping. Direct sequencing of amplified PCR products is the gold standard method, followed by phylogenetic analysis of clinical material. The aim of this study was to determine genotypes of HCV-infected patients with thalassemia in Golestan Province, Iran. Materials and Methods: This cross-sectional study included 217 patients (mean age: 21.82 ± 16 years, 50.7% male) with thalassemia major. Enzyme-linked immunosorbent assay (ELISA) was used for detection of HCV antibodies. Positive HCV-Ab samples were confirmed by reverse transcription polymerase chain reaction (RT-PCR) and sequencing. HCV genotypes were determined by aligning nucleotide sequences of patients with the standard nucleotide sequences obtained from GenBank (accession number: AB520610). Results: Of 217 patients with thalassemia major, 14 (6.45%) were found as anti-HCV-positive in the ELISA test. Among them, two patients (14.28%) had positive RT-PCR results. In addition, all patients were infected with HCV genotype 1a. Conclusions: Genotype 1a is the predominant HCV genotype in patients with thalassemia major in the Golestan province, Iran. KEYWORDS: Hepatitis C virus, Genotype, Thalassemia major, Golestan Province